Tindak Tutur Ilokusi Dalam Web Series “Nurut Apa Kata Mama” di Kanal Youtube Solusi BCA Dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Nurkhofifah, Nanda; Juansah, Dase Erwin; Firmansyah, Dodi (Peneliti.net, 2025)
This research aims to describe the form of illocutionary speech acts in the web series “According to What Mama Says” in episodes 1-4 on the Solusi BCA youtube channel and the implications for Indonesian language learning in high school. The research method used in this research is a qualitative descriptive method. Research data was analyzed using skillful-free involved listening and note-taking techniques. The forms of illocutionary speech acts found in the web series Nurut Apa Kata Mama in episodes 1-4 are (1) the assertive illocutionary speech act of stating, (2) the directive form of the illocutionary speech act of ordering, (3) the commissive form of the illocutionary speech act of promising, and offering, (4) the illocutionary speech act expressing praise, and (5) the illocutionary speech act expressing deciding and allowing.